Targeting: The Challenges of Modern Warfare - Ducheine, Paul A.L; Schmitt, Michael N.; Osinga, Frans P.B (T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2016)
XVI, 299 p. 6 illus., 1 illus. in color.